2018
DOI: 10.1188/18.cjon.e92-e96
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Screening: Appraisal of a Tool to Identify Patients’ Symptom Management and Advance Care Planning Needs

Abstract: Using the PAST seems to improve the identification of patients with palliative needs, leading to better management of symptoms. The PAST is also likely useful in facilitating the completion of advance directives, but this requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…The literature discussion about criteria to be used and the domains to be assessed, beyond the stage of the disease, already considered in all trials, includes symptoms, psychosocial distress, prognosis, trigger disease-related events and critical care planning issues 4 37–39. A number of PC need screening and assessment instruments have been developed and sometimes tested,39–50 but only a few of them were specifically designed to improve appropriate selection of cancer patients for referral to outpatient specialised PC 4 51. In the study by Paiva et al , the use of the PC referral tool would have increased referral rate by 3.2-fold 51.…”
Section: Discussionmentioning
confidence: 99%
“…The literature discussion about criteria to be used and the domains to be assessed, beyond the stage of the disease, already considered in all trials, includes symptoms, psychosocial distress, prognosis, trigger disease-related events and critical care planning issues 4 37–39. A number of PC need screening and assessment instruments have been developed and sometimes tested,39–50 but only a few of them were specifically designed to improve appropriate selection of cancer patients for referral to outpatient specialised PC 4 51. In the study by Paiva et al , the use of the PC referral tool would have increased referral rate by 3.2-fold 51.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic symptom assessment and standardized care pathway need to be established and utilized in the oncology setting. Flaherty and colleagues (2018) developed a 10-question Palliative Assessment Screening Tool (PAST), which was used by staff nurses during the admission or transfer assessment of patients. The tool was purposely composed of a limited number of questions so that it would be fast and easy to complete.…”
Section: Discussionmentioning
confidence: 99%
“…As life expectancy and chronic disease continue to rise, palliative care has become a high priority for health care systems. Palliative care improves the quality of life, symptom burden, and patient satisfaction for patients with life-limiting and chronic illnesses while ensuring proper resource use and creating cost savings 1-3 . These benefits fulfill the Institute for Healthcare Improvement's Triple Aim of focusing on improving the patient experience of care and the health of populations while reducing health care costs 4 .…”
mentioning
confidence: 99%
“…Early palliative care for inpatient hospitalizations, regardless of patient acuity and level of care, is often defined as within 3 days of admission 6 . Research has demonstrated that timely identification of patients with a serious, life-limiting illness and referral within 3 days of a hospital admission improves patient-reported outcomes and is essential to providing early and effective palliative interventions 1,2,6,7 …”
mentioning
confidence: 99%
See 1 more Smart Citation